2016
DOI: 10.1039/c6cp03638d
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene decomposition on Ir(111): initial path to graphene formation

Abstract: The complete mechanism behind the thermal decomposition of ethylene (C 2 H 4 ) on Ir(111), which is the first step of graphene growth, is established for the first time employing a combination of experimental and theoretical methods. High-resolution x-ray photoelectron spectroscopy was employed, along with calculations of core level binding-energies, to identify the surface species and their evolution as the surface temperature is increased. To understand the experimental results, we have developed a reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…In Table 1 Next, C-C bond breaking barriers (in blue) are between 0.6 and 2.1 eV, and, in most cases, are higher than dehydrogenation barriers (0.22-1.35 eV). However, in order to find probable reaction paths, it is important to include C-C cleavage processes, the most favorable of which can still compete with dehydrogenation processes 18 and play an important role.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Table 1 Next, C-C bond breaking barriers (in blue) are between 0.6 and 2.1 eV, and, in most cases, are higher than dehydrogenation barriers (0.22-1.35 eV). However, in order to find probable reaction paths, it is important to include C-C cleavage processes, the most favorable of which can still compete with dehydrogenation processes 18 and play an important role.…”
Section: Resultsmentioning
confidence: 99%
“…However, relative binding energies, i.e. differences with respect to a reference system (e.g., an adsorbed ethylene molecule), have been validated for a set of systems 34,18 and are accurate within 20-50 meV 34 . This accuracy comes from the fact that the core relaxes in similar ways when a C atom experiences different chemical environments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that U 0 +F vib 0 term is cancelled out in the difference. Next, we have to calculate the chemical potential µ of the monomer gas of carbon atoms on the surface at temperature T. Note that carbon atoms preferentially occupy hcp lattice sites 5 and hence one C atom can be assigned to a single lattice site. In this case, we have a distribution of N carbon atoms on N sites sites on the surface giving N sites !/[N!…”
Section: A Derivation Of Cluster Formation Energymentioning
confidence: 99%
“…Recent work has shown that ethylene (which is often used for graphene growth) deposited on the Ir(111) surface at room temperature with subsequent heating to higher temperatures, will decompose completely into carbon monomers. 5 These act as building blocks for the carbon clusters that go on to form graphene islands. In order to develop a clear understanding of graphene nucleation, the required initial stage of graphene growth, it is necessary to investigate the thermodynamics of the formation of carbon clusters on transition metal surfaces.…”
Section: Introductionmentioning
confidence: 99%